The goddess inheritance - Carter, Aimée, 1986- (Carter, Aimée, 1986- Goddess test novel., 2013)
"During nine months of captivity, Kate Winters has survived a jealous goddess, a vengeful Titan and a pregnancy she never asked for. Now the Queen of the Gods wants her unborn child, and Kate can't stop her--until the King of the Titans offers a deal. In exchange for her loyalty and devotion, the King of the Titans will spare humanity and let Kate keep her child. Yet even if Kate agrees, he'll destroy Henry, her mother and the rest of council. And if she refuses, the King of the Titans will tear the world apart until every last god and mortal is dead"--P. [4] of cover.